EXERCISES FOR ORGANIZING EXERCISES IN SPORTS AND DETERMINING MAIN GOALS - Sultanov Bakhtiyor Samatovich (Proximus Journal Publishing, 2024)
The article analyzes the means of organizing and improving the quality of sports training, and offers and recommendations are given in the article. Also, the main guidelines for organizing training in sports were defined, and detailed information was given about the exercises that should be performed during the training
Keywords: sport; result; purpose